Cost-benefit analysis of implementing a solar powered water pumping system ? A case study - Mishra A.K.; Sudarsan J.S.; Suribabu C.R.; Murali G. (Elsevier Ltd, 2025)
Solar-powered water driving scheme (SPWDS) has been successfully employed as a practical solution to guarantee reliable water supply in various hilly regions without electrical infrastructure. The Water Supply Systems / Schemes (WSS) focus on using pumping systems for delivering potable water to the community but face practical difficulties and financial hurdles at different implementation stages. These challenges encompass the practical complexities, the absence of non-renewable energy sources, and ongoing expenses for consumable and non-consumable items incurred during the water project's execution and maintenance. The present research study evaluates the performance of four water supply systems in Nepal which use solar energy as their primary power source. The key performance indicators are assessed, including the functionality index for facility distribution. Additionally, the research aims to evaluate the feasibility of transitioning from non-renewable to sustainable renewable energy source to achieve net zero energy consumption. This evaluation concentrates explicitly on calculating the cost-effectiveness index as a key metric. A proportional analysis is undertaken to evaluate the cost-benefit of the SPWDS, considering both the potential advantages and challenges associated with these initiatives. The present study affirms the technical feasibility and economic viability of operating a WSS using renewable and eco-friendly solar energy as the power source. This finding opens avenues for reducing energy consumption and contributes significantly to developing a policy framework to for tapping solar energy. ? 2024